A Journey with a Refugee Family: Raising Culturally Relevant Teaching Awareness. (December 2014) - Berumen, Freyca Calderon; Silva, Cecilia
Abstract : In a context that is increasingly becoming more diverse, we consider it essential to promote activities to develop linguistic and cultural awareness among preservice teachers. This chapter is based on the narratives of college students who when enrolled in an English as a Second Language class participated in a project where they accompanied newly resettled refugee families on their first visit to their children's school. Using narrative inquiry, the authors analyze the students' experience and describe the impact it had on them. The students' reflections provide evidence of their developing cultural awareness. The authors conclude that teacher educators can engage preservice students in authentic experience aimed at developing cultural awareness.